The optimal timing for non-culprit percutaneous coronary intervention in patients with multivessel coronary artery disease: A pairwise and network meta-analysis of randomized trials - Feng, Yujia; Li, Shu; Hu, Sihan; Wan, Jing; Shao, Hua (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Recently, several randomized trials have shown that patients with multivessel disease (MVD) often pursue complete revascularization during percutaneous coronary intervention (PCI) to improve their prognosis. However, the optimal time for the non-culprit artery has been controversial. This study aimed to determine the optimal strategy for revascularization in ST-segment elevation myocardial infarction (STEMI) patients with multivessel coronary artery disease (CAD). Methods Randomized controlled trials (RCTs) comparing three revascularization strategies [i.e., complete revascularization at the index procedure (CR), complete revascularization as a staged procedure (SR), or culprit-only revascularization (COR)] in STEMI patients with multivessel coronary artery disease were included. We performed both pairwise and network meta-analyses. Network meta-analysis was performed using mixed treatment comparison models. Results 17 trials with 8568 patients were included. In the network meta-analysis, the most interesting finding was that staged revascularization increased the risk of major adverse cardiac events (MACE) compared with complete revascularization at the index procedure [odds ratio (OR): 1.93; 95% confidence interval (CI): 1.07–3.49]. In the pairwise meta-analysis, complete revascularization reduced the incidence of MACE [risk ratio (RR): 0.62, 95% CI: 0.48–0.79, p < 0.001], mainly because it reduced the probability of unplanned repeat revascularization (RR: 0.49, 95% CI: 0.33–0.75, p = 0.001). There were no significant differences in all-cause mortality, cardiac mortality, or nonfatal re-myocardial infarction (MI). Conclusion Our analysis suggests that complete revascularization should be performed in STEMI patients with multivessel coronary artery disease, and complete revascularization at the index procedure is superior to staged revascularization in reducing the risk of MACE events.